Personal Qualities in The Structure of The Subject of Pedagogical Activity (Eurasian Journal of Learning and Academic Teaching, 2021)
The article considers about the general definition of the personality traits of a teacher, the professional and pedagogical qualities of the personality, personal orientation in the structure of the subject of pedagogical activity, professional self-awareness in the structure of the subject of pedagogical activity, the teacher as a subject of pedagogical work and the definition of pedagogical abilities.